Cerebral small vessel disease burden and cognitive and functional outcomes after stroke: A multicenter prospective cohort study. Issue 4 (25th July 2022) - Georgakis, Marios K.; Fang, Rong; Düring, Marco; Wollenweber, Frank A.; Bode, Felix J.; Stösser, Sebastian; Kindlein, Christine; Hermann, Peter; Liman, Thomas G.; Nolte, Christian H.; Kerti, Lucia; Ikenberg, Benno; et al.
Abstract: Introduction: It remains unknown whether the global small vessel disease (SVD) burden predicts post‐stroke outcomes. Methods: In a prospective multicenter study of 666 ischemic and hemorrhagic stroke patients, we quantified magnetic resonance imaging (MRI)–based SVD markers (lacunes, white matter hyperintensities, microbleeds, perivascular spaces) and explored associations with 6‐ and 12‐month cognitive (battery of 15 neuropsychological tests) and functional (modified Rankin scale) outcomes. Results: A global SVD score (range 0–4) was associated with cognitive impairment; worse performance in executive function, attention, language, and visuospatial ability; and worse functional outcome across a 12‐month follow‐up. Although the global SVD score did not improve prediction, individual SVD markers, assessed across their severity range, improved the calibration, discrimination, and reclassification of predictive models including demographic, clinical, and other imaging factors. Discussion: SVD presence and severity are associated with worse cognitive and functional outcomes 12 months after stroke. Assessing SVD severity may aid prognostication for stroke patients. Highlights: In a multi‐center cohort, we explored associations of small vessel disease (SVD) burden with stroke outcomes. SVD burden associates with post‐stroke cognitive and functional outcomes. A currently used score of SVD burden does not improve the prediction of poor outcomes. Assessing the severity of SVD lesions adds predictive value beyond known predictors. To add predictive value in assessing SVD in stroke patients, SVD burden scores should integrate lesion severity.